A qualitative study of a Sporting Memories program in South Australia: belonging, participation, and social connection - Laidlaw, Robert John; McGrath, Richard; Kumar, Saravana; Adams, Caroline; Murray, Carolyn M. (Frontiers in Public Health, 2024)
Background Older people can experience health and social challenges such as loneliness, depression, and lack of social connectedness. There is need for programs and approaches that address the growing incidence of social isolation and loneliness for older people. One initiative that aims to address these challenges is the Sporting Memories program. This program was developed in the United Kingdom and licensed to South Australia in 2019. The program is currently delivered across six community locations. Methods The aim of this study was to explore participants perspectives of the Sporting Memories program in South Australia. Underpinned by qualitative research, three focus groups were conducted, led by an experienced interviewer. Focus groups occurred at three of the six locations, including a day respite center, assisted living center and a government community center. The data were analyzed thematically by the research team. Results There were 16 participants over 65 years old, including four women and 12 men. Three key themes were developed: “free to talk about anything,” “not feeling left out” and “a chance to share and learn.” Collectively, participants reflected on how they built social connections, felt safe and included and learnt more about each other. Conclusion The Sporting Memories program provides a group program for older people to come together and develop new friendships. The use of sports as a means of reminiscence was considered relatable for the participants who reported social benefits and plans to keep attending. They valued learning through the program which was enhanced by having a facilitator who was knowledgeable about sport.